2015
DOI: 10.1080/15384047.2015.1056413
|View full text |Cite
|
Sign up to set email alerts
|

MiR-302c-3p suppresses invasion and proliferation of glioma cells via down-regulating metadherin (MTDH) expression

Abstract: Glioma is the most common malignant brain tumors with poor prognosis. The molecular events involved in the development and progression of glioma remain unclear. In this study, the expression levels of miR-302c-3p were examined in glioma tissues by qRT-PCR. The in vitro and in vivo functional effects of miR-302c-3p were examined further. Luciferase reporter assays were conducted to confirm the targeting associations. Results showed that the expression level of miR-302c-3p in glioma tissues was significantly low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Other studies have demonstrated that miR-145-5p targeted the 39-UTR of MTDH and restored its expression (26,33,34). MTDH is a reported oncogene that is elevated in a variety of cancers and contributes to tumor growth and metastasis (35,36). In our present study, the expression patterns of MTDH mRNA and protein were in accordance with SNHG1 serving as a miR-145-5p reservoir.…”
Section: Discussionsupporting
confidence: 85%
“…Other studies have demonstrated that miR-145-5p targeted the 39-UTR of MTDH and restored its expression (26,33,34). MTDH is a reported oncogene that is elevated in a variety of cancers and contributes to tumor growth and metastasis (35,36). In our present study, the expression patterns of MTDH mRNA and protein were in accordance with SNHG1 serving as a miR-145-5p reservoir.…”
Section: Discussionsupporting
confidence: 85%
“…Although not reported in colon cancer, some DEMs, such as miR-302c-3p [26], miR-487a [30] miR-638 [31], have been found involved in the survival, invasion or chemoresistance of several cancer cell lines. We also identified 26 novel significant DEMs in colon adenoma samples when compared with healthy subjects, some of which have previously reported as tumor-related miRNAs, such as miR-22 [37], miR-620 [38], miR-765 [39], and miR-1247 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study reported that the expression of miR‐302c was downregulated among GC patients . Moreover, recent researches have suggested that miR‐302c is implicated in many cancer‐related biological mechanisms, including cell proliferation and invasion, by targeting several genes, such as CDK2, MTDH, AKT1, and IL8 . Altogether, the current study aimed to investigate the association of miR‐302c INDEL (rs199971565) with GC susceptibility as a putative prognostic biomarker.…”
Section: Introductionmentioning
confidence: 95%
“…It has been well evidenced that some miRNAs can function as oncogenes or tumor suppressors in various types of cancers by involving in several different biological processes including differentiation, cell proliferation, and apoptosis . As a member of the miR‐302 family, miR‐302c plays critical roles in the development of many cancers including GC, glioma, and hepatocellular carcinoma . Interestingly, a prognostic value in GC patients has been suggested for miR‐302c …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation